(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2015)
The article deals with the linguistic and mental STATE concept represented in the Ukrainian aphorisms stock. The paper investigates the concept semantics content revealed inthe individual author’s expressions with nuclear and peripheral components. The article is also focused on some techniques and devices used to achieve appropriate stylistic effect.